PHOSPHORUS CONTENT IN THE LOWLAND RICE (Oryza sativa L.) DERIVED FROM P-FERTILIZER AND ORGANIC MATTER - Aisyah D. Suyono; Ania Citraresmini (Pusbindiklat - LIPI, 2011)
A pot experiment was conducted at the experiment station PATIR – BATAN, in order to determine phospho-rous content derived from P-fertilizer and organic matters in paddy ﬁ eld, both quantitatively and qualitatively. In the experiment, factorial pattern of Randomized Group Design with 3 replication was used. The ﬁ rst factor was the dose of SP-36 with four doses, which were 0, 30, 60, and 90 kg ha/SP-36. The second dose was organic fertilizer with four doses, which were 0, 5, 10, dan 15 ton/ha. 32P isotope technique with A-value methode was used to determine the absorption of P by the plants in order to establish the composition of P derived from the soil, 32P, SP-36 and organic fertilizer. The results of the experiment proved that an increase in the P content from one of the P sources caused a decrease in the P content from other P sources.